Thermophysical properties and enhancement behavior of novel B4C-nanoadditive RT35HC nanocomposite phase change materials: Structural, morphological, thermal energy storage and thermal stability - Öztop, Hakan Fehmi; Gurgenc, Ezgi; Gur, Muhammed (Elsevier, 2024)
This study aims to enhancement the thermal conductivity of RT35HC, as a commercial paraffin, by integrating boron carbide (B4C) nanoparticles for the first time, thereby producing B4C-nanoadditive nanocomposite PCMs. The B4C nanoparticles were reinforcement to RT35HC at mass fraction percentages (wt.%) of 0.5, 1, 1.5 and 2 by melting and physical mixing method. The structural and morphological characteristics of both pure and nanocomposite PCMs were examined using XRD, FT-IR, FE-SEM, and EDX. Thermal properties were investigated through DSC, TGA/DTA, and thermal conductivity measurements using the KD2-Pro device. The Gaussian process regression (GPR) model was used to analyze the Cp values in relation to temperature and additive ratio. Structural and morphological analysis results indicated a homogeneous distribution of nanoparticles within the PCM matrix, without any significant chemical or physical alterations. The introduction of B4C-nanoadditive did not markedly affect the melting and solidification temperatures. However, melting and solidification enthalpies decreased proportionally with increased nanoadditive ratios, with the greatest reductions being 7.44 % and 5.74 % at a 2 wt% nanoaddition rate, respectively. As the nanoadditive ratio increased, the thermal conductivity (k) and specific heat capacity (Cp) of RT35HC in both solid and liquid-phases enhanced significantly. Specifically, solid-phase (25 degrees C) k values increased by 67.51 % from 0.197 to 0.33, and liquid-phase (50 degrees C) k values by 15.29 % from 0.170 to 0.196. The highest Cp values in the solid and liquid-phases were measured as 3.01 and 2.49, respectively, in the nanocomposite with a high nanoadditive ratio. The GPR method yielded a success rate of 0.9015. Additionally, the nanocomposites exhibited enhanced thermal stability and higher thermal decomposition temperatures. Based on these characterizations, the fabricated B4C-nanoadditive nanocomposite PCMs show promise for application in TES and TM systems.
Keywords: Phase change material; Thermal energy storage; RT35HC; B4C; Nanocomposite PCM